ANALISIS FAKTOR DETERMINAN PELAKSANAAN TINDAK LANJUT HASIL PEMERIKSAAN BPK RI TERHADAP KINERJA PEMERINTAH PROVINSI PAPUA BARAT - Kurniawan, Agus; Salle, Agustinus; Hafizrianda, Yundy (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2024)
The completion of the BPK RI TLHP which is a manifestation of the performance of the West Papua Provincial government is reflected in the reconciliation data for follow-up monitoring in 2021 until the second semester of December 2021. From the Follow-up Monitoring Report of the Audit Board Audit Results for Semester II of 2021 number: 69/PTL/XIX.MAN/12/2021 dated December 17, 2021 for the 2005 to 2021 fiscal year period, the total number of findings is 548 with 1472 recommendations, the recommendation value is IDR. 364,202,688,959.23. The suboptimal completion of the TLHP indicates that there are problems in the implementation of the BPK TLHP in West Papua Province by the West Papua Regional Inspectorate TLHP Team, this can be seen in the data from 2005 to the second semester of 2021 from the results of the reconciliation of PTL LHP, the percentage of completion of the Follow-up is only 70.04%, this is due to the lack of optimal support / involvement of all parties in the implementation of TLHP as a form of accountability. The results of research by testing variables using the SmartPLS application show that the variables of commitment, SOP, competence and communication as a whole influence each other in the form of a path model; SOP affects commitment, SOP affects competence, Commitment affects competence, and competence affects communication. The overall path relationship is significant below 5 percent. Determinant indicators reflected in the high commitment of the leadership consist of: the ability of the leadership to motivate employees in the spirit of creating a work team, the ability of the leadership to motivate employees to complete the recommendation target, and the ability of the leadership to coordinate regarding the results of the examination. The indicators that improve the quality of the follow-up SOP are: clarity of the flow that must be done on the results of the examination, the ability of employees to understand the contents of the SOP, and the application of the SOP in the examination follow-up activities.